ANALISIS PRODUKSI CABAI SKALA USAHA MIKRO DI KABUPATEN KEPAHIANG - Irfan Dani; Retno A. Ekaputri (Universitas Bengkulu, 2019)
The aim of this research is to find out the influence of chili prices, chili production in the previous year, land area, price of leek on the chili supply in Kepahiang regency. This study covers the period 2004-2018, using secondary data in the form of panel data which is analyzed using multiple linear regression and the existing data is processed using the Eviews 9.0 computer program. The results of data analysis showed that the independent variable was the price of chili, the previous year's chili production and the area of land were positive and had a significant influence on the dependent variable that is chili production. While the price of scallion has a negative coefficient value and does not have a significant influence on chili production in Kepahiang regency.Keywords: Chili Prices, Chili Production , Land Area, Previous Year's Chili Production, Price Scallion